2022
DOI: 10.3389/ijph.2022.1604489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Same-Sex Marriage Legalization for Sexual Minority Men in Taiwan: Findings From a Prospective Study

Abstract: Objective: On May 24, 2019, same-sex marriage (SSM) was legalized in Taiwan. Increasing research in western countries has yielded longitudinal evidence about the psychosocial benefits of SSM for sexual minority individuals, but they have rarely included sexual minority-specific measures or considered participants’ relationship status. This study aimed to examine the short-term effects associated with the legalization of SSM for gay and bisexual men in Taiwan.Methods: A panel sample of 731 gay and 132 bisexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…9 To the best of our knowledge, there are no Asian or Japanese studies regarding SGM with national representativeness. A few Asian studies evaluating specific cohorts have reported that SGM is marginalized [10][11][12] , whereas much of the literature has been conducted in Western countries. The paucity of evidence could be attributed to certain Asian countries' opposition to the aforementioned United Nations resolution regarding SGM.…”
Section: Introductionmentioning
confidence: 99%
“…9 To the best of our knowledge, there are no Asian or Japanese studies regarding SGM with national representativeness. A few Asian studies evaluating specific cohorts have reported that SGM is marginalized [10][11][12] , whereas much of the literature has been conducted in Western countries. The paucity of evidence could be attributed to certain Asian countries' opposition to the aforementioned United Nations resolution regarding SGM.…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan also made history on May 24, 2019, by becoming the first Asian country to legalize same-sex marriage. 1 As a result of the increasing prevalence of transgenderism, there has been a rise in patients with gender dysphoria who are seeking sex reassignment therapy, which involves hormone therapy and gender reassignment surgery.…”
mentioning
confidence: 99%
“…In recent years, Taiwan has emerged as one of the most welcoming countries for the lesbian, gay, bisexual, and transgender community in Asia, and there has been a rise in transgender individuals as well as acceptance of diversity in gender identity. Taiwan also made history on May 24, 2019, by becoming the first Asian country to legalize same-sex marriage 1 . As a result of the increasing prevalence of transgenderism, there has been a rise in patients with gender dysphoria who are seeking sex reassignment therapy, which involves hormone therapy and gender reassignment surgery.…”
mentioning
confidence: 99%